The Effects of Flipped Classroom on EFL Students’ Autonomy and Motivation : English (GIST – Education and Learning Research Journal, 2024)
This study examined the effects of teaching English using the Flipped Classroom Model (FCM) on EFL (English as a Foreign Language) students' autonomy and motivation. The students' perceptions of flipped language instruction were explored to conduct a detailed analysis of the implementation. A mixed-method research design, an explanatory sequential design, was used with 50 EFL students at a Turkish state university during the spring term of the 2022-2023 academic year. A quasi-experimental design was used to create a control (n = 25) and an experimental (n = 25) group. To collect quantitative data, both groups were pre-tested with two scales at the start of the term (the Attitude/ Motivation Test Battery and the Autonomy Perception Scale). The FCM was used to teach main course lessons to the experimental group in a preparatory school while the control group was trained using a traditional learning approach. At the end of the term, both groups were post-tested after eight weeks of implementation in the experimental group. The qualitative data were collected via semi-structured interviews conducted at the end of the implementation to assess the participants' perceptions and perspectives on the impact of the flipped classroom. SPSS 25.00 was used to analyze quantitative data. To assess the effects of the intervention paired sample t-tests and independent sample t-tests were used. Descriptive content analysis was used to analyze qualitative data. The findings of this study indicate that the FCM, if properly implemented in L2 main course classes, has the potential to significantly increase autonomous learning and motivation. In comparison to the traditional model, flipped learning offers benefits such as making learning more enjoyable, increasing students' self-confidence, and decreasing their fear of making mistakes.
Keywords: flipped classroom; autonomy; motivation; english language teaching